Uncomplicated post-dated pregnancy in one horn of bicornis bicollis uterus - Bedi, Preet Kamal; Saini, Arunima; Bhagat, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Mullerian anomalies result from abnormal fusion of mullerian ducts (paramesonephric ducts). The prevalence of 1-10% is seen in general population. Patients with uterine anomalies have chances of infertility, miscarriage, preterm labor, cervical incompetence and are an independent risk factor for uterine rupture. Just a few pregnancies are carried forward till term without any maternal and fetal complications. Here we report a rare case of bicornuate uterus bicollis that successfully conceived, carried her pregnancy beyond her expected date of delivery (4 days overdue) and delivered a full-term baby without any significant complications.